Pseudomecânica: partículas de spins inteiros, semi-inteiros e fracionários - Pazetti, M [UNESP] (Universidade Estadual Paulista (Unesp), 2007)
We use the pseudomechanics to study non relativistic particles and massive and massless relativistic particles, all of them with spin. In this last case massless, we have two situations: in the first one, we built an invariant action of reparametrization, local transformations of SUSI and O(N) transformations. After the quantization, for the special case N=2, we obtain an action that describes both sectors of massless DKP theory. In a second situation, the action, which is constructed to be invariant under SUSY transformations and 'gama'-reparametrizations even when an interaction field is including, was obtained by including twistor variables. The commutation relations for these variables show that the particle states have fractional statistics and spin. Furthermore, we introduced a possible massive term for the non-interacting model. In all of these cases, the method of Dirac for constraint systems was used

Utilizando a pseudomecânica, estudamos partículas não relativísticas e partículas relativísticas massivas e não massivas, todas com spins. Neste último caso não massivo, fizemos duas abordagens: na primeira, construímos uma ação invariante por reparametrização, transformações de SUSY locais e transformações de O (N). Após a quantização, para o caso especial N = 2, obtivemos uma ação que descreve ambos os setores de DKP sem massa. Na segunda abordagem, a ação, que é invariante por reparametrização e transformações de SUSY locais mesmo quando um campo de interação é adicionado, foi obtida por meio da inclusão de variáveis twistores. As relações de comutação para essas variáveis nos revelam que o estado de partículas possui estatística e spin fracionários. Além disso, introduzimos um possível termo massivo para o modelo não interagente. Em todos os casos, o método Dirac para sistemas vinculados foi utilizado
Keywords: Teoria de campos (Física); Field theory (Physics)